NUMBERING OF AGRICULTURAL LANDS - Aytmuratov B. Sh.; Naubetova G. (European Science Publishing, 2024)
The purpose of this work is to develop the theoretical basis of digitalization of agricultural land use and monitoring of their condition. The main tasks of the research are solved by methods of comparative analysis. Integration of existing and developing information systems in agriculture, monitoring of agricultural land use was carried out.
Keywords: agriculture